2019
DOI: 10.1093/nar/gkz612
|View full text |Cite
|
Sign up to set email alerts
|

Novel enzymatic single-nucleotide modification of DNA oligomer: prevention of incessant incorporation of nucleotidyl transferase by ribonucleotide-borate complex

Abstract: Terminal deoxynucleotidyl transferase (TdT), which mediates template-independent polymerization with low specificity for nucleotides, has been used for nucleotide extension of DNA oligomers. One concern is that it is difficult to control the number of incorporated nucleotides, which is a limitation on the use of TdT for single-nucleotide incorporation of DNA oligomers. Herein, we uncovered an interesting inhibitory effect on TdT when ribonucleotide substrates (rNTPs) were employed in a borate buffer. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…13,14 The methods of chemical synthesis of DNA have signicantly facilitated the introduction of desired functionalities onto a specic position, 15 and post-synthetic modication methods are also powerful chemical tools, [16][17][18][19] especially for labeling of DNA targets with large labeling groups incompatible during the chemical synthesis process. [20][21][22] Bioinspired enzymatic postsynthetic labeling technologies have emerged as useful approaches through sequence-or structure-dependent substrate recognition, 23 and chemical modication is an alternative means for site-specic DNA labeling by incorporation of a chemical handle that is inert toward endogenous chemical functional groups but reactive toward a labeling reagent. 24,25 However, despite the remarkable advance of the bioconjugation technologies during the past decades, site-specic chemical modication remains a serious challenge due to its demanding criteria which include adequate reactivity of the labeling reagents toward the target site and high selectivity in biomolecule-compatible solvents such as aqueous buffer.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The methods of chemical synthesis of DNA have signicantly facilitated the introduction of desired functionalities onto a specic position, 15 and post-synthetic modication methods are also powerful chemical tools, [16][17][18][19] especially for labeling of DNA targets with large labeling groups incompatible during the chemical synthesis process. [20][21][22] Bioinspired enzymatic postsynthetic labeling technologies have emerged as useful approaches through sequence-or structure-dependent substrate recognition, 23 and chemical modication is an alternative means for site-specic DNA labeling by incorporation of a chemical handle that is inert toward endogenous chemical functional groups but reactive toward a labeling reagent. 24,25 However, despite the remarkable advance of the bioconjugation technologies during the past decades, site-specic chemical modication remains a serious challenge due to its demanding criteria which include adequate reactivity of the labeling reagents toward the target site and high selectivity in biomolecule-compatible solvents such as aqueous buffer.…”
Section: Introductionmentioning
confidence: 99%
“…This activity is of major importance in the diversification of immunoglobulins and T cell receptors in the process of V(D)J recombination of the adaptive immune system via random addition of nucleotides to nicked DNA strands. 4 , 5 TdT’s unique ability to mediate template-independent polymerization has made it a valuable tool in a variety of molecular biology applications including finding strand breaks, 6 modifying DNA oligomers with various NTPs, 7 and identifying DNA damage and epigenetic modifications. 8 Furthermore, the enzyme has proven useful for the generation of polynucleotides of high molecular weight 9 and amphiphilic structures upon extension with BODIPY-dUTP, 10 for detection of DNA and RNA on surfaces, 11 , 12 and immobilization of DNA on solid supports.…”
mentioning
confidence: 99%
“…The average step-yield is 97.7%, which is comparable with the performance of early phosphorylated amidine DNA synthesis [35,53]. A major challenge in TdT synthesis is the control of the addition of single bases, since TdT enzymes tend to catalyze the addition of multiple bases per cycle [65]. Although the synthesis of ssDNA by TdT is still an emerging strategy, several challenges remain.…”
Section: Terminal Deoxynucleotidyl Transferasementioning
confidence: 66%
“…Terminal deoxynucleotide transferase (TdT) is a polymerase that indiscriminately adds deoxynucleotide triphosphates (dNTPs) to the 3 end of an ssDNA, which makes it a natural candidate for enzymatic ssDNA synthesis (Figure 2a) [62,63]. TdT is characterized by low substrate specificity for nucleotides and template-independent polymerization [64], which makes TdT-based ssDNA synthesis methods compatible with various modified nucleotides and convenient subsequent purification [65]. Recent studies have shown that the coupling time of C, G, and T is 1.5 min while that of A is 3 min [53].…”
Section: Terminal Deoxynucleotidyl Transferasementioning
confidence: 99%
See 1 more Smart Citation